2016
DOI: 10.1371/journal.pone.0168489
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Rubber Hand Illusion Are Related to Sensory Suggestibility

Abstract: In the rubber hand illusion (RHI), watching a rubber hand being stroked in synchrony with one’s own hidden hand may induce a sense of ownership over the rubber hand. The illusion relies on bottom-up multisensory integration of visual, tactile, and proprioceptive information, and on top-down processes through which the rubber hand is incorporated into pre-existing representations of the body. Although the degree of illusory experience varies largely across individuals, the factors influencing individual differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 35 publications
(75 reference statements)
5
72
1
Order By: Relevance
“…It seems that, when PN was absent, our patient was not susceptible to experience the illusion of fake hand ownership. A failure in experiencing the RHI is not by itself a sign of a defective body representation, and the lack of the illusion is in line with the literature showing individual differences in the subjective feeling of ownership induced by the RHI (Haans, Kaiser, Bouwhuis, & IJsselsteijn, 2012;Marotta, Tinazzi, Cavedini, Zampini, & Fiorio, 2016). Therefore, in the absence of a pathological bodily condition (i.e., PN), the patient correctly integrated visual and tactile information delivered between his own and a fake hand, but this multisensory integration did not lead to an alteration of the subjective sense of hand ownership for both the right (first and second sessions) and the left (second session) hands.…”
Section: Discussionsupporting
confidence: 86%
“…It seems that, when PN was absent, our patient was not susceptible to experience the illusion of fake hand ownership. A failure in experiencing the RHI is not by itself a sign of a defective body representation, and the lack of the illusion is in line with the literature showing individual differences in the subjective feeling of ownership induced by the RHI (Haans, Kaiser, Bouwhuis, & IJsselsteijn, 2012;Marotta, Tinazzi, Cavedini, Zampini, & Fiorio, 2016). Therefore, in the absence of a pathological bodily condition (i.e., PN), the patient correctly integrated visual and tactile information delivered between his own and a fake hand, but this multisensory integration did not lead to an alteration of the subjective sense of hand ownership for both the right (first and second sessions) and the left (second session) hands.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we have previously shown that intranasal OXT modulates the processing of affective touch in a context-dependent manner rather than altering touch perception per se (Scheele et al, 2014;Kreuder et al, 2017). Thus, our data suggest that the amygdala may play an important role in multisensory integration of temporally congruent tactile, visual, and proprioceptive information (i.e., bottom-up processes in the RHI) or may be involved in the integration of external stimuli into one's own body representation (i.e., top-down processes in the RHI; Marotta et al, 2016). Importantly, the observation that a complete absence of the RHI in a subsample of five participants was not associated with significantly larger amygdala volumes underscores the importance of multisensory integration in other brain areas like the premotor cortex (Ehrsson et al, 2004) or the temporoparietal junction (Olivé et al, 2015).…”
Section: Discussionmentioning
confidence: 71%
“…"), and ownership feelings toward the rubber hand (Item 3: "I felt as if the rubber hand were my hand."). Item 3 has been found to be particularly informative to quantify susceptibility for body ownership illusions, whereas Items 1 and 2 are instead closely related to touch localization (Marotta et al, 2016). We thus operationalized "illusion vividness" as the mean response to RHIQ items 1-3 (for a similar approach, see Morgan et al, 2011), whereas the single response to Item 3 was defined as "body ownership experience".…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results imply that haptic feedback devices can alter human body experience and foster the subjective embodiment of non-corporal limb avatars. Even though the experience of bodily illusions can vary largely across individuals [55], the exertion of tactile feedback yielded significantly increased subjective embodiment. In particular, the embodiment questionnaire by Longo [18] indicates that certain experiences of ownership were additionally increased if force feedback was provided.…”
Section: Proprioceptive Driftmentioning
confidence: 99%